Repurchase Intention of Halal Cosmetic Product Among Muslim Consumers: The Roles of Islamic Branding, Halal Awareness, and Trust - Anita Rahmawaty; Ita Rakhmawati (IQTISHADIA, 2022)
This study aims to examine the effects of Islamic branding and halal awareness on trust and repurchase intention. It also investigates the roles of trust in mediating the effects of Islamic branding and halal awareness towards repurchase intention of halal cosmetic products in Kudus regency. The research data is elicited from 275 Muslim consumers of halal cosmetic products in Kudus. The analysis technique of the collected data uses Partial Least Squares Path Modeling (PLS-SEM). The study finding shows that Islamic branding and halal awareness significantly affect consumers’ trust and repurchase intention in positive ways. Trust mediates the effects of Islamic branding and halal awareness towards repurchase intention of halal cosmetic products in Kudus. The finding also intends to contribute to Sharia business players comprehending the factors that improve trust and repurchase intention towards the halal cosmetic products for their business development.